Enhancing Conclusion Sections in Final Year Project Presentations: An Engineering Perspective - Wan Raihan, Wan Shaaidi; Noor Raha, Mohd Radzuan; Wan Jumani, Fauzi (Semarak Ilmu Publishing, 2024)
The Final Year Project Presentation or FYPP is an essential academic oral presentation for tertiary students across various university courses and fields. Despite its importance, there exists a notable lack of comprehensive understanding about the genre, particularly about the conclusion section. This study aimed to investigate engineering students' perception of the good characteristics of the conclusion section in FYPP. A questionnaire survey was administered to a sample of 33 engineering students, who identified the following features as important components of the conclusion section: a summary of the final year project, presentation of overall findings, references to previous research, discussion of issues related to the final year project, restatement of the objective/focus, specific results, interpretation of results, significance of the results, limitations, counter-arguments, and an explanation of the final year project. The study reveals that students are aware of the various elements that make up the conclusion section and suggests that this knowledge can help them improve their FYPPs. By better understanding the genre expectations and characteristics, engineering students can present their final year project findings more effectively and demonstrate their mastery of the discipline.